Peningkatan Daya Saing Produk UMKM melalui Digitalisasi Proses Produksi dan Manajemen Persediaan di Kelurahan Sepanjang, Kecamatan Sepanjang, Kabupaten Sidoarjo - Widiar Onny Kurniawan; Nurdina; Yuni Sukandani; Mutiara Rachma Ardhiani; Munir Rachman (Ekobis Abdimas, 2025)
This community service activity aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) products through digitalization of production processes and inventory management. The activity was carried out in Sepanjang Village, Sepanjang District, Sidoarjo Regency, from April 20 to June 20, 2025. The main problems faced by MSMEs in this area are low operational efficiency due to manual recording, weak stock management, and lack of understanding of digital technology. The method of implementing the activity includes initial observation, counseling, training in digital applications for production management and inventory, and ongoing assistance. The results of the activity show that MSMEs are able to gradually adopt digital technology, increase efficiency in production time and costs, reduce recording errors, and maintain stock availability more accurately. Furthermore, this transformation also has an impact on improving the quality of customer service and strengthening the competitive position of MSMEs in the local market. This activity makes a real contribution to the empowerment of technology-based MSMEs and forms a more adaptive and sustainable business ecosystem.